Epitranscriptomic RNA m6A Modification in Cancer Therapy Resistance: Challenges and Unrealized Opportunities - Mohammad Burhan Uddin; Zhishan Wang; Chengfeng Yang (Advanced Science)
Abstract Significant advances in the development of new cancer therapies have given rise to multiple novel therapeutic options in chemotherapy, radiotherapy, immunotherapy, and targeted therapies. Although the development of resistance is often reported along with temporary disease remission, there is often tumor recurrence of an even more aggressive nature. Resistance to currently available anticancer drugs results in poor overall and disease‐free survival rates for cancer patients. There are multiple mechanisms through which tumor cells develop resistance to therapeutic agents. To date, efforts to overcome resistance have only achieved limited success. Epitranscriptomics, especially related to m6A RNA modification dysregulation in cancer, is an emerging mechanism for cancer therapy resistance. Here, recent studies regarding the contributions of m6A modification and its regulatory proteins to the development of resistance to different cancer therapies are comprehensively reviewed. The promise and potential limitations of targeting these entities to overcome resistance to various anticancer therapies are also discussed.